Hypoglycemic medicines in the treatment of Alzheimer’s disease: Pathophysiological links between AD and glucose metabolism - Wang, Yixuan; Hu, Hao; Liu, Xinyu; Guo, Xiangyu (Frontiers in Pharmacology, 2023)
Alzheimer’s Disease is a global chronic disease in adults. The pathological mechanism of AD is still not fully elucidated. Diabetes Mellitus is a high-risk factor for AD in epidemiology. The central nervous system can also respond to glucose metabolism except for peripheral systems. Impaired glucose-related pathways in DM cause damage to the brain in the pathogenesis of AD. Emerging evidence has revealed that dysregulation of insulin signaling and mitochondrial function could be causative links between AD and DM. Some antidiabetic medicines are effective in the treatment of AD. This may be due to abnormalities of glucose metabolism. Metformin is beneficial for cognitive decline and AD, although results from clinical trials studies were inconsistent. The research on GLP-1 receptor agonists is also emerging. Exendin-4 has an effect on AD in animal models. Liraglutide and dulaglutide have been proven to benefit AD in clinical trials, but semaglutide is lack of clinical evidence. Some novel GLP-1 Ras have therapeutic effects on AD. Studies have proven that DPP4 inhibitors could benefit cognitive function such as saxagliptin, vildagliptin, linagliptin, and sitagliptin in animal models. And sitagliptin can enhance cognitive performance in clinical trials. SGLT2 inhibitors were considerably more protective in T2DM patients against new-onset dementia compared to DPP4 inhibitors. Empagliflozin and dapagliflozin have neuroprotective effects on AD. Insulin therapy is a promising therapy but some studies indicated that it may increase the risk of AD. Plants are important precursors of many chemical drugs, especially hypoglycemic drugs. Hypoglycemic agents widely used in clinical such as metformin and SGLT2is are prototypes from herbal plants. It has been revealed that herbal medicines, as well as herbal compounds and components, are effective in cognitive improvement and neuroprotection in the brain. For example, polyphenols, alkaloids, glycosides, and flavonoids have protective benefits in cognition and glucose metabolism. Focusing on insulin signaling, the article aims to summarize the pharmacological mechanism of hypoglycemic drugs and herbal medicines. New strategies for the treatment including antidiabetic synthesized drugs and herbal medicines may be provided to patients with AD. More clinical trials are needed to produce definite evidence for the effectiveness of hypoglycemic medications.